Translation Activities in the Ottoman Empire - Aksoy, Berrín (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn the Ottomans, translation activities took place without much significance until the 18th century. Due to the dominance of religion and the closed society structure, mostly texts on Islamic civilization and arts from Arabic and Persian were translated in the form of commentaries, explanations and footnotes. The only contribution of translation then may be said to be the promotion of written Ottoman Turkish which was used in Anatolia as well as among the Court circles. With the beginning of Westernization efforts in the 18th and largely in the 19th centuries, translation activities gained momentum and proliferated in kind and quantity. A large amount of books from the West and the East in the fields of science, literature, arts, social sciences, etc. were translated during that time. Although these activities were disorganized and inconsistent, they still helped the development of similar sciences and Modern Turkish Literature which was to reach its peak in the Modern Turkish Republic established in the 20 th century.